Immunohistochemical Analysis of CYP11B2 (Aldosterone Synthase) and Evaluation of the HISTALDO Classification in Patients with Primary Aldosteronism - Karadepe, Mustafa; Yanar, Hande; Binokay, Hülya; Erdoğan, Şeyda; Akkus, Gamze (Current Molecular Medicine, 2025)
ObjectivePrimary Aldosteronism (PA) is the most common cause of secondary hypertension. Immunohistochemical analysis of PA is based on specific monoclonal antibodies targeting CYP11B1 and CYP11B2, which are enzymes responsible for the aldosterone production in the adrenal cortex. The recently proposed HISTALDO classification introduced CYP11B2 immunohistochemistry to define clinically relevant diagnostic categories. We aimed to investigate the relationship between clinical characteristics and immunohistochemistry of CYP11B2 in PA and also evaluate staining in cortisol-producing cells by comparing patients with Cushing’s Syndrome (CS). Consecutive patients diagnosed with PA (n=21) and CS (n=20) were included between 2015-2022. All of them underwent unilateral adrenalectomy in our tertiary center.MethodsFollowing hematoxylin and eosin (H&E) staining of the pathological specimens, all slides were re-evaluated and immunostained for CYP11B2. A semiquantitative H-score was assessed for each patient and compared with staining intensity. Patients with PA were grouped and classified according to the HISTALDO classification.ResultsThe mean size of adenoma in patients with PA was much smaller compared to patients with CS (p=0.001). An increase in the immunohistochemical H-score of the patients with PA (121.36 ±81.04 vs 73.94±57.70, p=0.045) was observed in comparison to the patients with CS. When comparing the patients with PA according to HISTALDO criteria, the H-score of the patients with Aldosterone Producing Adenoma (APA, n=10) was 136.6±78.86 compared to the non-APA group, which was 86.81±85.3 (n=11, p=0.05). Moreover, mean preoperative aldosterone levels (p=0.06) and aldosterone-to-renin ratio (ARR, p=0.03) were higher in patients with APA compared to non-APA patients. Response to surgical therapy was more favorable in patients with APA than the patients with non-APA.ConclusionCYP11B2 is a key enzyme responsible for the synthesis of aldosterone. CYP11B2 expression, as assessed by immunostaining, was associated with the clinical characteristics, severity of PA, and response to the treatment. Hence, immunohistochemical analysis of CYP11B2 should be incorporated into the routine clinical workup to better localize aldosterone-producing cells.
Keywords: immunohistochemistry